THE UTILIZATION OF GALERKIN-PSO METHOD FOR SOLVING INTERPOLATION-LIKE PROBLEM - FITRI YANTI (NIM : 10108082); Pembimbing : Prof. Dr. Iwan Pranoto, AYU
The interpolation-like problem discussed here is to search an optimal curve minimizing a functional cost and at the same time interpolating several given points. Instead of solving the optimization problem with constrain directly, we approximate the problem with a pure optimization problem without constrain. After that, the Galerkin Method is used to make the problem a finite dimensional one. The problem becomes finding a minimal point and value of a finite dimensional function. The Particle Swarm Optimization (PSO) algorithm is used to minimize this function.